2009
DOI: 10.1536/ihj.50.701
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Triple Antiplatelet Therapy Including Triflusal and Conventional Dual Therapy in Patients Who Underwent Drug-Eluting Stent Implantation

Abstract: SummaryTriflusal is a derivative of acetylsalicylic acid but it exhibits different pharmacological and pharmacokinetic properties. The object of this study was to evaluate the efficacy of additional use of triflusal in patients who underwent drug-eluting stent implantation.First, we prospectively tested platelet function with a rapid platelet function analyzer (VerifyNow Ⓡ -Aspirin) in patients with stable angina (male, age, 61.6 ± 8.3, body weight, 69.3 ± 11.2 kg) who maintained dual (aspirin 100 mg and clopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…In this study, the he prevalence of aspirin resistance was analogous to the prevalence found in previous reports 4)22)23). On the other hand, the prevalence of clopidogrel resistance was very high and was above the range of prevalence that has been reported in the literature.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In this study, the he prevalence of aspirin resistance was analogous to the prevalence found in previous reports 4)22)23). On the other hand, the prevalence of clopidogrel resistance was very high and was above the range of prevalence that has been reported in the literature.…”
Section: Discussionsupporting
confidence: 88%
“…Antiplatelet agent resistance is a known risk factor for thromboembolic complication 4)22)23). In this study, the he prevalence of aspirin resistance was analogous to the prevalence found in previous reports 4)22)23).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations